DVFx, and modernization of technology: audience’s changing taste in the 21st century - Hasrul Hashim, (Penerbit Universiti Kebangsaan Malaysia, 2019)
The changes from analogue to digital in the film industry occurred rapidly and triggered a change in the landscape, especially in the usage of digital visual effects (DVFx). Thus, films that use the digital visual effects have developed a demand for technology exploitation among audiences. The most powerful effect afforded by digitization is the changes in the relationship between film and audience, especially in the aspect of cinema spectacle. Previously, the use of digital visual effects served merely to fix or modify damaged or negative elements in the post-production process, but it also has contributed to transformation of the tastes of audiences in 21st century cinemas. Tastes and aesthetic judgments are manifestations of aspects of class inequality and social, cultural and reproduction ideology. To evaluate tastes especially within different systems of society is not a simple matter as there has been a change in various aspects of society due to technological advances. This judgment involves complex processes and variables. This paper explored how globalization impacts audiences’ changing tastes with the juxtaposition of the digital visual effects revolution. The research used qualitative research methods, which is focus group discussions involving three groups of moviegoers from Malaysia, India and Australia. The analysis of the findings is divided into two main themes: modernization and technology. In general, the findings show that taste among movie audiences is a typical representation of the middle class society.